2001
DOI: 10.1063/1.1342799
|View full text |Cite
|
Sign up to set email alerts
|

CoNi/Pt interface roughness probed by nonlinear magneto-optics, x-ray scattering and atomic force microscopy

Abstract: The crystallographic contribution of the nonlinear magneto-optical response from CoNi/Pt interfaces appears to scale linearly with increasing interface roughness as determined by small angle x-ray scattering and atomic force microscopy. From the magnetic contribution it follows that the increased interface roughness causes the interface moment to turn out of plane while the bulk of the film has an in-plane magnetization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…For the isotropic case or for the (001) surface of a cubic crystal there are c Magneto-optical effects in the SHG from surfaces have been discussed in theoretical papers of Pan et al [11] and Hü bner and Bennemann [12] and have been demonstrated experimentally soon after [13][14][15]. Meanwhile a large number of publications have proven MSHG as a valuable tool for the investigation of magnetism at surfaces and interfaces [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…For the isotropic case or for the (001) surface of a cubic crystal there are c Magneto-optical effects in the SHG from surfaces have been discussed in theoretical papers of Pan et al [11] and Hü bner and Bennemann [12] and have been demonstrated experimentally soon after [13][14][15]. Meanwhile a large number of publications have proven MSHG as a valuable tool for the investigation of magnetism at surfaces and interfaces [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%